Vol. 3, No. 1, September 2021 - Bonar HP Panjaitan (Scientia Regendi, 2021)
These days, there are still digital platform application development companies and clients as the owners who do not see information security as an asset that needs to be invested. This is because of the results cannot be seen directly in profits, so this is often ignored by companies. Based on primary data in a case study of a development company, most client companies are still more concerned with making applications completed on time and running smoothly. There is no attention on information security. That’s why the developed applications have many security holes or vulnerabilities that become targets for hackers. Usually the companies will only focus on information security after an incident that causes a loss. Developers who are competent on awareness of information security should give companies confidence to invest resources in the security of the developing digital platform applications. With good information security standards, application systems will become more resilient to cyber attacks. And from the development side, the development time will not dragged much and is still within limits, and ofcource the expenses will not bloat.